Safety and immunogenicity of pentavalent rotavirus vaccine in a randomized, double-blind, placebo-controlled study in healthy elderly subjects - Lawrence, Jody (Hum Vaccin Immunother, 2014)
Rotavirus may be an important causative agent of acute gastroenteritis (AGE) in the elderly, a population that is particularly vulnerable due to waning immunity. It is estimated that rotavirus may account for 2–5% of adult gastroenteritis hospitalizations in the United States. This is the first study to assess the safety and immunogenicity of the live pentavalent rotavirus vaccine (RV5) in an elderly population. In this study, healthy, independently living adults aged 65–80 years were randomized in a 2:1 ratio to receive three 2-mL oral doses of RV5 or placebo administered 28–42 days apart. All subjects were followed for safety for 42 days post any vaccination and up to 180 days after the final vaccination for clinical adverse events. Immunogenicity of RV5 was measured by serum anti-rotavirus IgA enzyme immunoassay and serum neutralizing antibody responses to human rotavirus serotypes prior to and after each dose. Results of this study demonstrated that RV5 was generally safe and well tolerated in healthy elderly adults, where 9% of placebo and 27% of RV5 recipients experienced a vaccine-related adverse event of mild or moderate intensity. Immune responses (serum anti-rotavirus immunoglobulin A [IgA] and serum neutralizing antibodies against human rotavirus serotypes in the vaccine) were augmented in this population after a single dose of RV5, despite the factors of older age and preexisting antibodies to the virus. Therefore, if vaccination in the elderly is needed, further evaluation of RV5 as a candidate vaccine in this age group may be warranted.